Aktualne problemy nauki prawa ochrony środowiska - Ciechanowicz-McLean, Janina (Studia Prawnoustrojowe, 2019)
Many environmental problems can only be addressed through international agreements with domestic legislation. This acts both globally and locally. Many Multilateral Environmental Agreements – MEA are classifed in soft law in international public law. Sustainable development is a principle of law. Genetically Modifed Organisms are imported in agriculture, food productions but not accepted by the human population. Human rights to the environment must in future be used like hard law.